Challenges of People Management in MEMOS Software - Zwinger, Michal; Pauknerová, Daniela, 1970-; Králová, Tereza, 1978-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
Organically growing companies usually reach a point when people management starts to be challenging up to such scale that influences their further development. This master thesis in its first part covers basic topics essential for people management, especially communication, work motivation, job design and leadership. In the second part of this work is focus put on empiric research of a concrete situation inside the selected company, analyses of management interviews and employee questionnaires. The last part then presents a set of recommendations adjusted directly for the researched company in order to help improve current situation.
Vedoucí práce: Daniela Pauknerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses